2002
DOI: 10.1088/0268-1242/17/7/303
|View full text |Cite
|
Sign up to set email alerts
|

Strained Si/SiGe n-channel MOSFETs: impact of cross-hatching on device performance

Abstract: The performance of surface channel MOSFET devices depends on the Si/SiO 2 interface quality. The present study has examined the Si/SiO 2 interface of strained Si n-channel MOSFETs fabricated on a Si/SiGe virtual substrate. Evidence of a variation in the oxidation rate of strained Si along the cross-hatch period is presented. The undulating oxide thickness was found to be accompanied by increased nanoscale roughness at the Si/SiO 2 interface for the strained Si surface channel devices compared with conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 38 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…The greater dependence of on for the strained Si device may be indicative of slightly higher gate oxide interface roughness than that of the control device. This may arise, for example, from Ge segregation from the SiGe layers into the Si channel leading to nonuniform oxidation rates [12] and consequently gate oxide interface roughness. Interference of Ge during gate oxidation additionally causes de- graded electrical properties of oxides.…”
Section: Device Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater dependence of on for the strained Si device may be indicative of slightly higher gate oxide interface roughness than that of the control device. This may arise, for example, from Ge segregation from the SiGe layers into the Si channel leading to nonuniform oxidation rates [12] and consequently gate oxide interface roughness. Interference of Ge during gate oxidation additionally causes de- graded electrical properties of oxides.…”
Section: Device Resultsmentioning
confidence: 99%
“…Although it has been shown that a strained layer can be grown on a given alloy composition material to a thickness greater than without relaxation [11], so-called "metastable" material cannot withstand the high thermal budget processing commonly used in MOS fabrication. Consequently, most researchers have attempted fabrication of strained Si/SiGe MOSFETs using reduced thermal budgets and/or by lowering the alloy compositions, ultimately sacrificing the performance gains achievable [12]- [14].…”
mentioning
confidence: 99%
“…Although no independent characterisation (i.e. TEM) is available to verify this claim, such defects are known to pose a problem and can be reduced with further optimisation of the epitaxial growth [7]. Nonetheless, combined low-V DS I-V and C-V measurements on long-gate FETs, yielded a drift channel mobility of 20 cm 2 /(V s), at room temperature, indicating that the material quality could, indeed, be an issue.…”
Section: Measurements and Discussionmentioning
confidence: 99%
“…The misfit and threading dislocations in the strained Si layer can essentially affect the device performance [4][5][6]. An additional factor affecting the device performance is the cross-hatching, a large-scale roughness inherent in such structures due to the stress fields associated with the underlying misfit dislocations generated during relaxation in the graded SiGe layer [7].…”
Section: Introductionmentioning
confidence: 99%